The effect of the simulated intrauterine sound on behavioral and physiological indices of pain during capillary blood sampling for screening preterm infants: a randomized clinical trial study - Shamimeh Yarahmadi; Moluk Pouralizadeh; Zahra Atrkarroushan; Parichehr Shahroudi (BMC Pediatrics, 2024)
Abstract Introduction Due to medical procedures, preterm infants are at high risk for side effects of pain. In this regard, heel lancing for capillary blood sampling is a common painful procedure. The present study was conducted to assess the effectiveness of a simulated intrauterine sound on behavioral and physiological indices of pain due to heel-prick blood sampling in preterm infants. Methods A double‑blind randomized clinical trial (RCT) was conducted. The data were collected from September 23 to December 22, 2019. We measured the effect of a simulated intrauterine sound on changes in the behavioral and physiological parameters of pain (heart rate, SPO2) caused by heel lance that was measured 5 min before the intervention, during the sampling, and 5 min after the procedure. We measured behavioral pain by video recording the infants’ faces and then the scoring neonatal infant pain scale (NIPS). Heart rate and SPO2 were measured using a pulse oximeter device. The data were analyzed using analysis of variance (ANOVA) and independent t‑test in SPSS software version 20.0. Results Eighty infants were randomized (40 in each group). Mean scores NIPS during and after intervention were in the intervention group (3.55 ± 0.84, 95% CI: 3.30–3.80(, and (1.15 ± 0.84, 95%: 0.95–1.35) and in the control group (5.57 ± 0.95, 95% CI:5.30–5.85) and (3.00 ± 0.98) respectively. There were significant differences in scores of NIPS between the two study groups during (p < 0.001) and five min after heel lancing (p < 0.001). Mean scores of heart rate in the three phases of before, during, and five min after the intervention were respectively in the intervention group (127.57 ± 4.45, 95% CI:126.27-128.99), (131.07 ± 6.54, 95% CI:129.20-133.22), (128.45 ± 5.15, 95% CI:127.02-130.07) and in the control group (128.67 ± 4.57, 95% CI:127.32-130.07), (136.07 ± 7.24, 95% CI:133.90-138.37), and (132.42 ± 6.47, 95% CI:130.37-134.49). There were significant differences in heart rate between the intervention and the control group during (p = 0.002) and five min after the heel lance (p = 0.003). Mean scores of SPO2 in the three phases of baseline, during, and five min after the intervention were respectively in the intervention group (96.72 ± 0.93, 95% CI:96.42-97.00), (91.47 ± 1.46, 95% CI:91.05–91.92), (94.17 ± 1.03, 95% CI:93.22-94.00) and in the control group (96.6 ± 0.84, 95% CI:96.35–96.85), (91.5 ± 1.24, 95% CI:91.12–91.87), and (93.60 ± 1.27, 95% CI:93.85–94.50). Conclusion This study showed that the simulated intrauterine sound reduces the behavioral pain and heart rate in the intervention group during and after heel lance. These results suggest using the method during the painful heel lancing to reduce pain parameters in preterm infants.